Variability in larval period, post-setting growth and survival of the oyster Crassostrea belcheri produced by gamete stripping method - Tanyaros, Suwat; Tarangkoon, Woraporn (Agriculture and Natural Resources, 2016)
Gamete stripping is the most practical method in oyster production because the time of fertilization can be precisely controlled. However, it was found that there was much greater variability in the speed of egg development compared with natural spawning. In this study, three groups of larvae (aged 21, 27 and 29 d) were successively separated from fertilization to the pediveliger stage among all the larvae produced by the stripping method. No differences in the spat growth rate were found among the larval periods at 15 d of the experiment (p ≥ 0.05), but spat growth and survival rates of juvenile oysters in the larval periods of 21 and 27 d were significantly higher than those for 29 d at the end of the experiment (30 d). The positive correlation between larval growth rates and the spat daily yield at 30 d was significant. These results indicated that the gamete stripping method produced high variations in the larval period and post-setting growth and survival in the oyster, Crassostrea belcheri.